2015
DOI: 10.1007/s12598-015-0542-1
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution and formation mechanism of laser-ignited SHS joining between Cf/Al composites and TiAl alloys with Ni–Al–Ti interlayer

Abstract: In this study, C f /Al composites and TiAl alloys were joined by a new method named laser-ignited selfpropagating synthesis (SHS). Mixed powders of 63.0Ni-31.9Al-5.1Ti (wt%) were used as joining interlayer. Perfect joint was got. The microstructure evolution and formation mechanism of the SHS joint were investigated by scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS) and X-ray diffraction (XRD). Results show that localized melting occurs on both sides. One c-Ni 0.35 Al 0.30 Ti 0.35 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The interlayer products were a mixture of three phases. According to the phase diagram and previous studies [33,34], the dark phase (point F) was confirmed to be the NiAl phase. The gray reticular phase (point G) and white small block phase (point H) were supposed to be the Ni 3 Al 5 Zr 2 and Ni 2 AlZr, respectively.…”
Section: Joint Microstructuresupporting
confidence: 54%
“…The interlayer products were a mixture of three phases. According to the phase diagram and previous studies [33,34], the dark phase (point F) was confirmed to be the NiAl phase. The gray reticular phase (point G) and white small block phase (point H) were supposed to be the Ni 3 Al 5 Zr 2 and Ni 2 AlZr, respectively.…”
Section: Joint Microstructuresupporting
confidence: 54%
“…Self-propagation high-temperature synthesis(SHS)was proposed by Soviet scientist Merzhanov et al in 1967 [35]. Its principle is to induce internal chemical reaction by applying external energy to the material, and the heat released by the reaction promotes it to continue, so as to synthesize new materials [36][37].…”
Section: Self-propagation High-temperature Synthesis Weldingmentioning
confidence: 99%